Reducing the sodium content without modifying the quality of beef burgers by adding micronized salt - Rios-Mera J.D. (2019)
The authors are grateful to Dr. Izabela Dutra Alvim – Instituto de Tecnologia de Alimentos (ITAL, Campinas, Brazil), for the support with the LV 950-V2 equipment. Juan D. Rios-Mera, Erick Saldaña and Melina L. M. Cruzado-Bravo received the support of the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica – CONCYTEC, Peru (CIENCIACTIVA programme, PhD scholarship contracts: No. 238-2018-FONDECYT; No. 104-2016-FONDECYT; No. 241-2018-FONDECYT, respectively). Iliani Patinho received the M.Sc. scolarship of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – CAPES.